1995
DOI: 10.1063/1.358790
|View full text |Cite
|
Sign up to set email alerts
|

Optical constants and film density of TiNxOy solar selective absorbers

Abstract: Articles you may be interested inInvestigation of temperature dependent dielectric constant of a sputtered TiN thin film by spectroscopic ellipsometry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…Lazarov et al reported that TiO x N y thin films deposited on copper exhibited excellent solar selective properties [12,13] tandem absorbers [16]. We have reported the solar-absorbing coating based on TiAlON/TiAlN with regard to its colored appearance as energy-saving materials used in buildings [17].…”
Section: Introductionmentioning
confidence: 97%
“…Lazarov et al reported that TiO x N y thin films deposited on copper exhibited excellent solar selective properties [12,13] tandem absorbers [16]. We have reported the solar-absorbing coating based on TiAlON/TiAlN with regard to its colored appearance as energy-saving materials used in buildings [17].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, interest in titanium oxynitride films has increased and have been extensively studied due to their improved physical and chemical properties, which mainly depend on their N/O ratio. Oxygen-rich TiN x O y films have been used as insulating layer in metal-insulator-metal (MIM) capacitive structures to avoid interfacial oxide layer formation [11], while nitrogen-rich TiN x O y films have been used as an excellent diffusion barrier layer for semiconductor applications [12]; Additionally, many other useful applications of TiN x O y films, such as anti-reflective coating [13] and biomaterials [14] solar selective absorbers [15] and wearresistant coatings [16], have been demonstrated. The wettability studies to determine hydrophilic or hydrophobic nature of titanium oxynitride film are the area that is unexplored and no literature has been found regarding the investigation of this property so far.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Moreover, the presence of oxygen in titanium nitride films leads to a promising functional range of materials, TiN x O y , already used as solar selective absorbers, [5] or transparent windows for infrared detectors. [6,7] However, few works have been published on the growth, structure, and properties of these titanium oxynitride films.…”
Section: Introductionmentioning
confidence: 99%